Pengaruh permainan treasure hunt terhadap kemampuan siswa sekolah dasar dalam menganalisis materi arah mata angin - Luthfia Nur Andini; Diah Gusrayani; J Julia (COLLASE (Creative of Learning Students Elementary Education), 2025)
The current education development is facing challenges, one of which is the students' lack of ability to analyze and understand complex material in real-world context. This study aims to assess the impact of the treasure hunt game on students' ability in analyzing material about cardinal directions. The research method used is a quasi-experiment with a nonequivalent pre-test post-test control group design. The sample consists of two elementary schools: SDN Malaka as the experimental group and SDN Babakanbandung as the control group. The control group used the lecture method, while the experimental group participated in a treasure hunt game designed to enhance their understanding of concept and analytical skills about cardinal directions. The research instrument was in a fotm of an analytical ability test consisting of 20 multiple-choice questions. Data analysis using the t-test showed that the treasure hunt game had a significant impact on students' abilities. The N-Gain test results revealed that the average improvement in analytical ability in the control class was only 11.48% (low category), while in the experimental class it reached 80.00% (high category). Therefore, the treasure hunt game can significantly improve the ability to analyze cardinal directions compared to the lecture method.